Quantitative evaluation of potentially toxic elements and associated risks in Acrisols and Ferralsols of western Ghana - El Mellouki, Meryem; Boularbah, Ali; Kebede, Fassil (Frontiers in Soil Science, 2025)
This study investigates the natural distribution of potentially toxic elements in western Ghana as affected by soil types (i.e., Acrisols and Ferralsols). Geo-accumulation indices (Igeo), Enrichment Factor (EF), and risk index (RI) were computed to evaluate soil pollution classes, while the Soil Quality Index (SQI) was calculated to assess soil quality’s effect on pollution hazard. The study revealed subtle differences in contamination patterns: Acrisols exhibited slightly elevated Igeo values for elements such as Se, Mo, Fe, and Ti, suggesting localized enrichment possibly linked to natural processes or minor external inputs. In contrast, Ferralsols showed moderate Igeo values for Cr and Ni, indicating some enrichment consistent with parent material characteristics. EF values for all elements in both soil types were below 2, classifying them as “depletion to minimal enrichment” and confirming that elemental concentrations are predominantly of geogenic origin rather than anthropogenic inputs. Principal Component Analysis (PCA) effectively distinguished the two soil types, with Acrisols associated with higher trace metal concentrations and greater organic matter content, while Ferralsols were influenced more by Al and Fe oxides. Heatmap analysis further highlighted distinct element clustering, with Cr, Ni, and Se more prominent in Ferralsols, and Mo, Ti, and other trace elements showing spatial variation in Acrisols. These findings underscore the influence of pedogenic processes and mineral weathering in shaping elemental distributions across soil types in tropical environments and support a soil-type-specific management approach to ensure environmental protection and sustainable land use. The Soil Quality Index indicated that Ferralsols (SQI range: –2.65 to 1.78) had slightly lower surface horizon quality, likely due to leaching, while Acrisols (SQI range: –2.84 to 3.89) showed higher quality in deeper horizons, reflecting better nutrient retention.